North-South Trade-Related Technology Diffusion : Virtuous Growth Cycles in Latin America - Schiff, Maurice; Wang, Yanling (2012)
This paper examines the impact on total factor productivity in Latin America and the Caribbean (LAC) and in other developing countries of trade-related technology diffusion from the North) (denoted by NRD), education, and governance, research and development The NRD value for a developing country is an average of R&D stocks in the North, with weights related to openness with the North. Industry-specific NRD is based on the North s industry-specific R&D, North-South trade patterns, and input-output relations in the South. The main findings are: i) the impact of education and governance on TFP is significantly larger in LAC than in other developing countries, while the opposite holds for NRD; and ii) education, governance and NRD have additional effects on TFP in LAC s R&D-intensive industries through their interaction with either or both of the other two variables; and iii) since NRD increases with openness and with R&D in the North, both variables raise the South's TFP directly as well as through their interaction with education and governance. These interaction effects imply that increasing the level of any of the three policy variables -- education, governance, or openness --results in virtuous growth cycles. These are smallest under an increase in one of these variables, stronger under an increase in two of them and strongest under an increase in all three variables.